Esensi dan Eksistensi Ruang Pertunjukan Ritual Benjang Dengan Konsep Rasa Sahrdaya - Santi Salayanti; Sarwanto . (JURNAL RUPA, 2021)
Benjang ritual performance is a traditional performance born from cultural ceremonies that still survive and are carried out today, especially by the younger generation. Through the functional mindset and lifestyle of Bandung's young people today, Ritual Benjang is present through its distinctive features in the experience of quality ritual beauty and is believed to achieve the life goals of the people of Uj Berung Bandung. Furthermore, the show symbolizes the existence of Benjang as a medium to get closer to God and as a sports activity supporting sportsmanship. This study uses a qualitative method with observation and perception based on phenomena. The concept of taste Sahrdaya becomes a foundation for the entire layout of the space used in the ritual of the performance and the audience in living and even interacting at the Benjang mask show. The higher their understanding of the concept of taste, the stronger the sensibility in responding to attractive mask shows. Similarly, the aesthetic quality of the mask dance performance is also complementary in a ritual performance supported by the concept of taste. The success of the implementation of taste in this show provides aesthetic stimuli for the audience to achieve catharsis for them with the involvement of a sense that gives meaning in life and becomes a person who is always inferior.